Modified mathematical model for gas phase olefin polymerization in fluidized-bed catalytic reactor - Ibrehem, A.S.; Hussain, Mohd Azlan; Ghasem, N.M. (Elsevier, 2009)
A modified model for the gas phase catalyzed olefin polymerization fluidized-bed reactors (FBR) using Ziegler-Natta catalyst is presented in this study. This mathematical model accounts for mass and heat transfer between the bubbles and the clouds without chemical reaction, between the clouds and the emulsion without chemical reaction, and between emulsion and solid with chemical reaction that occurs at the surface of the catalyst particles. The model accounts for the effect of catalyst particles type and porosity on the rate of reaction. In this work, the concentration and temperature profiles in the bubble, and emulsion phases are calculated and the effect of catalyst solid phase on the system is estimated. The effect of important reactor parameters such as superficial gas velocity, catalyst injection rate, and catalyst particle growth on the dynamic behavior of the FBR is investigated and the behavior of mathematical model is compared with the reported models for the constant bubble size model, well-mixed model and bubble growth model. Moreover, the results of the model are compared with the experimental data in terms of molecular weight distribution and polydispersity of the produced polymer at steady state. A good agreement is observed between our model prediction and the actual plant data.